The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pone.0174026
|View full text |Cite
|
Sign up to set email alerts
|

Retinal oximetry measures systemic hypoxia in central nervous system vessels in chronic obstructive pulmonary disease

Abstract: BackgroundDetermination of the blood oxyhemoglobin saturation in the retinal vessels of the eye can be achieved through spectrophotometric retinal oximetry which provides access to the state of oxyhemoglobin saturation in the central nervous system circulation. The purpose of this study was to test the capability of the Oxymap T1 oximeter to detect systemic hypoxemia and the effect of supplemental oxygen on retinal vessel oxyhemoglobin saturation.MethodsOxygen saturation of hemoglobin in retinal arterioles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…6 Focal retinal hypoxia is thought to underlie the pathophysiology of many ocular diseases, such as diabetic retinopathy, 7,8 glaucoma, 9,10 and retinal venous occlusion. 11 Thus, the ability to image retinal oxygen gradients could be very valuable in treating and diagnosing retinal disease. Also, chorioretinal vasculature imaging has a significant role for diseases, such as neovascular age-related macular degeneration (AMD).…”
Section: Introductionmentioning
confidence: 99%
“…6 Focal retinal hypoxia is thought to underlie the pathophysiology of many ocular diseases, such as diabetic retinopathy, 7,8 glaucoma, 9,10 and retinal venous occlusion. 11 Thus, the ability to image retinal oxygen gradients could be very valuable in treating and diagnosing retinal disease. Also, chorioretinal vasculature imaging has a significant role for diseases, such as neovascular age-related macular degeneration (AMD).…”
Section: Introductionmentioning
confidence: 99%
“…The authors demonstrated that retinal oximetry detected lower oxyhaemoglobin saturation in patients with COPD breathing ambient air compared to healthy controls (Eliasdottir et al. ). Furthermore, they showed that retinal oximetry is able to capture an increase in retinal arteriole oxyhaemoglobin saturation when the COPD subjects inspired supplemental oxygen.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, measurement of oxyhaemoglobin saturation by retinal oximetry may be a more reliable and relevant method to determine organ oxygenation and hypoxia in patients with COPD than measurements of peripheral oxyhaemoglobin saturation (Heistad & Abboud 1980;Van de Louw et al 2001;Wilson et al 2010). Eliasdottir et al (2017) determined the blood oxyhaemoglobin saturation in the retinal vessels in patients with COPD, who were on long-term oxygen therapy based on the criteria for experiencing sustained hypoxia (defined as an arterial oxyhaemoglobin saturation of <90%), and healthy subjects. The authors demonstrated that retinal oximetry detected lower oxyhaemoglobin saturation in patients with COPD breathing ambient air compared to healthy controls (Eliasdottir et al 2017).…”
Section: Retinal Oximetrymentioning
confidence: 99%
See 1 more Smart Citation
“…The mean of the retinal SaO 2 readings by Oxymap, measured in healthy persons, was lower by 5% than finger SaO 2 , measured by pulse oximetry, with 95% CI of −2 to 12% [ 71 ]. Measurements of mean retinal SaO 2 in patients with systemic hypoxemia were lower by 2% with 95% CI of −3 to 11% compared to invasive femoral SaO 2 values [ 72 ]. No significant correlation was found between individual retinal and finger SpO 2 [ 72 , 73 , 74 ].…”
Section: Pulse Oximetry—theory and Techniquesmentioning
confidence: 99%